(untitled) (Journal of the College of Basic Education, 2026)
This research explores the latent mechanisms of meaning formation within the nebulous zone that precedes linguistic utterance—a state termed the "Nebula of Primacy" (Sadeem al-Bada’ah). In this realm, meaning manifests as a latent semantic potentiality within consciousness before conforming to the constraints of the linguistic system. This phenomenological approach conceives the "Implicit" (Al-Mudmar) as a vital space where vision is engendered as an intuitive structure, weaving together emotion, memory, and imagination. Consequently, creativity becomes an authentic act of revelation that generates meaning prior to its articulation, liberating language from its instrumental function to become an illuminative ascent (Mi’raj) connecting the self with existence. By navigating an intellectual intersection that bridges Al-Jahiz’s tradition of "proffered meanings" with Gadamerian hermeneutics and Peircean semiotics, the study asserts that understanding is a hermeneutic event arising from the fusion of the subjective horizon with that of the text. In this process, silence and the implicit emerge as active partners in discourse, serving as a mirror that reflects the mysteries of Being—mysteries that direct expression fails to encompass in their existential abundance.